Acoustic Metamaterials : Negative Refraction, Imaging, Lensing and Cloaking - Craster, Richard V. (Springer Series in Materials Science, 2013)
Over the past ten years, electromagnetic metamaterials have become ubiquitous in modern photonics research, following Pendry's proposal of a perfect flat lens via negative refraction at the turn of the millennium, and the related development of invisibility cloaks. These two paradigms have their counterparts in another emerging subject of wave motion: Acoustic metamaterials, which are locally resonant structures displaying an effective macroscopic behaviour (such as a negative density) beyond Newton's second law. Applications of acoustic metamaterials range from non-invasive probing and high-resolution tomography in medical imaging, to acoustic camouflaging and seismic protection.The twelve chapters constituting this book present an up-to-date survey of many aspects of acoustic metamaterials, including filtering effects, extraordinary transmission, subwavelength imaging via tomography or time-reversal techniques, cloaking via transformation acoustics and elastodynamics and even cloaking via acoustic scattering cancellation and active exterior cloaking. It is hoped that the variety of subjects touched upon in this book, and the ways in which they can be treated theoretically, numerically and experimentally give a grasp of the richness of the emerging topic of acoustic metamaterials and will contribute to initiate even more research activity and applications in the near future.The book will be a valuable reference for postgraduate students, lecturers and researchers working on acoustic metamaterials and the wider field of wave phenomena.